The Effect of Performance-Based Budget Management on The Achievement of Strategic Planning Targets at The Indonesian Quarantine Agency - Paremono Priatsaleh, Disti; Poltak Sinambela, Lijan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Law No. 17 of 2003 on State Finance introduced a performance-based budgeting approach to improve the efficiency, effectiveness, and transparency of public budget management. The Indonesian Quarantine Agency (BARANTIN) as a government institution has adopted this approach, but still faces obstacles in realizing the budget and achieving optimal performance targets. Uneven budget absorption every quarter and accumulating at the end of the year is the main challenge that hinders the maximum function of the State Revenue and Expenditure Budget (APBN). This study uses a descriptive method with a qualitative approach to analyze the role of performance-based budgeting in increasing the achievement of strategic targets in BARANTIN. Data were collected through observation, interviews, and literature studies, then analyzed descriptively. The results of the study are expected to provide recommendations for BARANTIN in optimizing the achievement of performance targets in accordance with strategic planning.